The Colloidal Properties of Nanocellulose. Issue 8 (28th February 2023) - Benselfelt, Tobias; Kummer, Nico; Nordenström, Malin; Fall, Andreas B.; Nyström, Gustav; Wågberg, Lars
Abstract: Nanocelluloses are anisotropic nanoparticles of semicrystalline assemblies of glucan polymers. They have great potential as renewable building blocks in the materials platform of a more sustainable society. As a result, the research on nanocellulose has grown exponentially over the last decades. To fully utilize the properties of nanocelluloses, a fundamental understanding of their colloidal behavior is necessary. As elongated particles with dimensions in a critical nanosize range, their colloidal properties are complex, with several behaviors not covered by classical theories. In this comprehensive Review, we describe the most prominent colloidal behaviors of nanocellulose by combining experimental data and theoretical descriptions. We discuss the preparation and characterization of nanocellulose dispersions, how they form networks at low concentrations, how classical theories cannot describe their behavior, and how they interact with other colloids. We then show examples of how scientists can use this fundamental knowledge to control the assembly of nanocellulose into new materials with exceptional properties. We hope aspiring and established researchers will use this Review as a guide. Abstract : Colloidal toolbox : Nanocelluloses are anisotropic nanoparticles of semicrystalline assemblies of glucan polymers with great potential as a renewable raw material for a more sustainable society. In this comprehensive overview, we describe the most prominent colloidal behaviors of nanocellulose based on classical and new theories and how controlling these colloidal interactions is a toolbox to guide the assembly of nanocellulose into new nanostructured materials.